2020
DOI: 10.1021/acsanm.0c00658
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-Based Etch Resist for Semiconductor Device Fabrication

Abstract: As the feature size of semiconductor devices decreases, the resist layer with high etch resistance is required to achieve fine pattern transfer during lithography. Conventional resists (e.g., amorphous carbon layers and polycyclic aromatic hydrocarbon films) have reached the limit of etch resistance. Here, we proposed graphene as an etch resist in lithographic process for future semiconductor device. First-principles simulation and experimental reactive ion etching (RIE) revealed that the etch resistance of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…In order to successfully produce high-quality monolayer graphene on a metal catalyst with high reliability, repeatability, and at a large-scale, many experimental growth parameters must be evaluated. , One of the most challenging decisions is choosing a robust metal catalyst on the growth substrate which provides the foundation for graphene growth. Previously, graphene growths on Ru, Ir, Pt, Ni, and Cu have been conducted, and electrical properties along with other properties of graphene have been analyzed. , The graphene growth mechanism using chemical vapor deposition (CVD) is different on different transition metals because of the different solubility of carbon atoms in these metals. , …”
Section: Introductionmentioning
confidence: 99%
“…In order to successfully produce high-quality monolayer graphene on a metal catalyst with high reliability, repeatability, and at a large-scale, many experimental growth parameters must be evaluated. , One of the most challenging decisions is choosing a robust metal catalyst on the growth substrate which provides the foundation for graphene growth. Previously, graphene growths on Ru, Ir, Pt, Ni, and Cu have been conducted, and electrical properties along with other properties of graphene have been analyzed. , The graphene growth mechanism using chemical vapor deposition (CVD) is different on different transition metals because of the different solubility of carbon atoms in these metals. , …”
Section: Introductionmentioning
confidence: 99%
“…Atomically thin graphene, known for its extraordinary properties of low bending stiffness, high mechanical strength, , deformability, , impermeability, , high etch resistance, and chemical stability, holds immense potential beyond its traditional role in electronic applications. Specifically, it has been reported that graphene has exceptional etching resistance to XeF 2 gas, which is renowned for its high selectivity toward silicon, leading to extensive applications in microcantilevers and micromachining devices .…”
Section: Introductionmentioning
confidence: 99%